The Mediating Role of Cognitive Emotion Regulation Strategies in the Relationship between Self-Compassion, Purpose, and Mental Health - Silva, C.; Andrade, S.; Guedes, E.; Melo, B.; Nobre, D.; Pereira, R.; Santos, A. C.; Matos, M.; Arriaga, P. (1st Annual Poster Blitz in Psychology of Health & WellBeing, 2025)
Mental health is a central component of well-being, and growing evidence supports the protective role of self-compassion, purpose and adaptive cognitive emotion regulation strategies (CERSs) in its promotion. Self-compassion, a mindful and caring approach to one's suffering, has been consistently linked to positive psychological outcomes and may promote mental health through adaptive strategies for regulating emotions. Likewise, purpose, a sense of meaning and direction in life, contributes to well-being and emotional resilience. Although prior studies linked self‑compassion, purpose and CERSs to mental health outcomes, their association and the mediating role of CERSs remain underexplored. This study investigated these relationships and whether CERSs mediate the relationship between self-compassion and purpose and mental health. A total of 367 participants (69.5% female, 29.2% male, 0.8% other; M = 37.6, SD = 12.96) completed an online survey including the ‘‘Self-compassion and Purpose’’ dimension of the Mindful Self-Care Scale (MSCS), the Cognitive Emotion Regulation Questionnaire – Short version (CERQ-Short), and the Short-Form 12 Health Survey (SF-12). Results indicated that the “self-compassion and purpose” dimension was positively associated with mental health and greater use of adaptive CERSs, and negatively associated with maladaptive strategies, which were in turn negatively related to mental health. However, mediation analyses showed that CERSs partially mediated the relationship between self-compassion and purpose and mental health. These findings highlight the importance of reducing the use of maladaptive CERSs, particularly catastrophizing and self-blame, and of promoting self-compassion and purpose as potential protective resources for mental health.